A VR-enabled intelligent hybrid system for maintenance - Li, Jingrong. (2008)
This research aims at realising a virtual reality (VR) enabled intelligent system for maintenance, known as V-REALISM. It deals with condition-based fault diagnosis, disassembly sequence planning for maintenance and desktop virtual reality.